1987
DOI: 10.1128/jcm.25.2.312-315.1987
|View full text |Cite
|
Sign up to set email alerts
|

Effect of agitation and frequent subculturing on recovery of aerobic and facultative pathogens by Roche Septi-Chek and BACTEC blood culture systems

Abstract: The positivity rate and time to recovery of pathogens were compared in Roche Septi-Chek (RSC-TSB) and BACTEC radiometric systems on 3,539 paired blood cultures. Both systems were steadily agitated, with frequent subculturing or processing of the RSC-TSB agar slides and BACTEC bottles, respectively, during the first 24 h of incubation. The RSC-TSB system recovered 249 pathogens (7.0% positivity rate), compared with 234 (6.6% positivity rate) isolates recovered from BACTEC. For the most common isolates, Staphylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…The agitation principle has been implemented in the processing of clinical blood cultures during the last 15 years, and experience has generally been positive (1,6,8,10,12,14,15,16,19,21,22). One reason why it has taken such a long time to adopt the agitation principle with respect to clinical blood cultures may be that many of the traditional visual signs of growth (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The agitation principle has been implemented in the processing of clinical blood cultures during the last 15 years, and experience has generally been positive (1,6,8,10,12,14,15,16,19,21,22). One reason why it has taken such a long time to adopt the agitation principle with respect to clinical blood cultures may be that many of the traditional visual signs of growth (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Several large-scale studies concerning the advantages of agitation have been performed, but they are difficult to interpret because of simultaneous variations in other parameters, e.g. blood volume and blood culture system (10,21,22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that agitation of aerobic vials increases the speed of different blood culture systems (9,11,15,28). The beneficial effect of agitation can probably be explained by a better oxygenation of the media, more even distribution of nutrients, and separation of bacteria from each other and from the leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…This was most likely due to the presence of reducing agents in the Signal medium (i.e., sodium pyruvate, sodium thioglycolate, cysteine hydrochloride, and dithiothreitol). Previous studies (3,6) suggested that the recovery of aerobic organisms could be improved with the use of agitation and terminal subcultures. However, we were unable to confirm this with the Signal system.…”
Section: Discussionmentioning
confidence: 99%